2016
DOI: 10.3390/ani6050028
|View full text |Cite
|
Sign up to set email alerts
|

Ranging Behaviour of Commercial Free-Range Laying Hens

Abstract: Simple SummaryCommercial free-range production has become a significant sector of the fresh egg market due to legislation banning conventional cages and consumer preference for products perceived as welfare friendly, as access to outdoor range can lead to welfare benefits such as greater freedom of movement and enhanced behavioural opportunities. This study investigated dispersal patterns, feather condition and activity of laying hens in three distinct zones of the range area; the apron area near shed; enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
4
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 25 publications
4
67
4
12
Order By: Relevance
“…This technology provides several advantages over more traditional flock estimates of range use because it allows the investigation of more differences between individuals within a flock in terms of ranging patterns. In both flocks in this study, over 60% of the hens accessed the range every day, and 85.6% and 97.1% (Flock A and Flock B, respectively) accessed the range area at least once, which is in contrast to previous research using point sampling that reported that very few hens accessed the range [6,10,20,25,26]. The present results are similar to previous research using individual tracking of hens in both experimental and commercial conditions.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…This technology provides several advantages over more traditional flock estimates of range use because it allows the investigation of more differences between individuals within a flock in terms of ranging patterns. In both flocks in this study, over 60% of the hens accessed the range every day, and 85.6% and 97.1% (Flock A and Flock B, respectively) accessed the range area at least once, which is in contrast to previous research using point sampling that reported that very few hens accessed the range [6,10,20,25,26]. The present results are similar to previous research using individual tracking of hens in both experimental and commercial conditions.…”
Section: Discussioncontrasting
confidence: 91%
“…There was also a moderate correlation between the number of days on which hens accessed the range and the total number of zones hens accessed on the range; hence the more time hens spent on the range, the more likely they were to venture farther from the shed. Previous research found that, at farther distances from the shed, fewer hens could be seen in the range [5,10]. However, the far range in the present study was closer to the shed than in other studies [5,10]; therefore it is possible that fewer hens do access the most distant parts of larger ranges.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations